Guidelines for Tool-Size Selection for Single-Point Incremental Forming of an Aerospace Alloy - Hussain, G.; Khan, H. R.; Gao, L.; Hayat, N. (Taylor & Francis Inc, 2013)
Single-point incremental forming (SPIF) is relatively a novel sheet forming process to produce small lots with low cost. In this article, guidelines for tool size selection for SPIF of an aerospace grade alloy (AA-2024) are presented. The role of tool size, with respect to sheet thickness employed, on the formability in SPIF (i.e., spifability) is clarified. The response surface method is employed in order to study the significance of sheet thickness (t o) and tool radius (r) on the spifability. The results of analysis of variance (ANOVA) show that the sheet thickness and tool radius are not significant individually, however, a strong interaction between these parameters exists. Moreover, for a particular sheet thickness, there exists only one r/t o value at which the spifability can be maximized under a given set of conditions. Furthermore, for a given sheet thickness, if a tool with radius lesser than a particular value is used (i.e., r/t o<2) the material squeezes out from the tool/sheet interface. And, such a condition adversely affects the material spifability. FEA using LS-DYNA has also been carried out.
Keywords: Radius; Regression; SPIF; Spifability; Thickness